Being your own boss and bossing others: The moderating effect of managing others on work meaning and autonomy for the self-employed and employees - Milena Nikolova; Boris Nikolaev; Christopher Boudreaux (Global Labor Organization (GLO), 2021)
We examine the moderating role of being a supervisor for meaning and autonomy of self-employed and employed workers. We rely on regression analysis applied after entropy balancing based on a nationally representative dataset of over 80,000 individuals in 30 European countries for 2005, 2010, and 2015. We find that being a self-employed supervisor is correlated with more work meaningfulness and autonomy compared with being a salaried supervisor working for an employer. Wage supervisors and self-employed supervisors experience similar stress levels and have similar earnings, though selfemployed supervisors work longer hours. Moreover, solo entrepreneurs experience slightly less work meaningfulness, but more autonomy compared with self-employed supervisors. This may be explained by the fact that solo entrepreneurs earn less but have less stress and shorter working hours than selfemployed supervisors.
Keywords: I31; L26; M10; 330; self-employment; supervisors; autonomy; work meaningfulness